SiC@Ag heterojunction filler, insulating coating and preparation method
Patent Information
- Application Number
- CN202610956023.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]本发明的目的是解决现有技术SiC颗粒化学镀银存在的镀层均匀性差以及银层与基体结合力弱的问题
本发明通过前处理工艺与镀液体系的协同调控,实现了银层在SiC颗粒表面的均匀、致密及高结合力沉积,并赋予了复合涂层显著的非线性电导效应。首先,针对SiC表面化学惰性及自然氧化层阻碍金属沉积的问题,本发明采用HF与NH4F复合粗化体系进行前处理,其原理在于HF能有效溶解SiC表面的SiO2氧化层,而NH4F的加入不仅提供氟离子缓冲维持刻蚀稳定性,更能在颗粒表面刻蚀构建纳米级粗糙结构和微坑洞,这种微观粗糙形貌极大增加了银层沉积的接触面积,并在银层与SiC基体间形成牢固的机械互锁作用,从而有效解决了现有技术中银层与基体结合力弱、易发生脱落或局部剥离的技术问题。在此基础上,本发明采用SnCl2/HCl敏化体系,利用Sn2+在酸性条件下的均匀吸附特性,在粗化后的粗糙表面原位构建出高密度的催化活性位点,其原理是为后续化学镀银提供必需的成核中心,克服了SiC表面缺乏催化活性导致的成核不足与局部漏镀问题,确保了银层的全面覆盖与均匀成核。
Smart Images

Figure CN122916730A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new materials technology, specifically relating to a SiC@Ag heterojunction filler, an insulating coating, and a preparation method thereof. Background Technology
[0002] Silicon carbide (SiC), as an important inorganic filler, possesses high hardness, excellent thermal stability, low coefficient of thermal expansion, corrosion resistance, and unique semiconductor properties, making it widely applicable in electrical insulation, protective coatings, and functional composite materials. Introducing SiC into insulating polymer systems not only improves the mechanical and thermal properties of the material but also allows its semiconductor characteristics to participate in interfacial electrical modulation. To further enhance the interfacial conductivity and electric field response of SiC particles, surface metallization modification is typically required. Silver, due to its excellent electrical and thermal conductivity, high chemical stability, and low interfacial resistance, is an ideal material for SiC surface metallization. By constructing a silver shell layer on the SiC surface, an Ag / SiC metal-semiconductor heterojunction can be formed, potentially enabling the construction of a conductive network with a significant field strength response within the polymer. This allows the composite material to exhibit nonlinear conductivity behavior characterized by low-field insulation and high-field conduction.
[0003] However, existing SiC electroless silver plating processes still face numerous technical bottlenecks, making it difficult to meet the application requirements of high-performance composite insulating coatings. Firstly, SiC particles are chemically inert, naturally lacking catalytically active sites, and their surfaces are often covered with naturally formed oxide layers and organic contaminants adsorbed during processing and transportation. When directly electroless-plating SiC with silver, problems such as insufficient nucleation, uneven deposition, localized missed plating, and silver layer agglomeration easily occur, making it difficult to form a continuous and dense metallic silver layer on the particle surface. Secondly, conventional silver plating pretreatment processes often fail to adequately remove the oxide layer and adsorbed contaminants from the SiC surface, failing to effectively construct a rough interface and active surface suitable for metal deposition. This directly results in severely insufficient adhesion between the deposited silver layer and the SiC substrate, making it prone to silver layer detachment or localized peeling during subsequent composite processing or use.
[0004] Furthermore, in traditional silver plating systems, the compatibility between the silver-ammonia complex system and the reduction system is often insufficient, making it difficult to coordinate and control the concentration of free silver ions and the reduction deposition rate in the plating bath. This mismatch easily leads to the spontaneous precipitation of silver ions in the solution, forming free silver slag, or rapid and uncontrolled local deposition on the particle surface, ultimately resulting in a rough, uneven coating and discrete macroscopic conductivity. For nonlinear conductive composite insulating coatings, the metallization quality of the filler surface directly determines the structural integrity of the Ag / SiC heterostructure interface and the field strength response capability of the conductive network in the polymer. If the silver layer on the filler surface is insufficiently covered, uneven in thickness, has poor adhesion, or exhibits significant agglomeration, local conductive pathways in the composite system will be difficult to establish stably, and the interface barrier distribution will be discrete. This results in a lack of significant conductivity improvement under high field strength, failing to achieve a stable and significant nonlinear conductivity effect, severely limiting its practical application in high-voltage insulation protection and other fields. Summary of the Invention
[0005] The purpose of this invention is to solve the problems of poor coating uniformity and weak adhesion between the silver layer and the substrate in the existing SiC particle electroless silver plating technology.
[0006] The objective of this invention is achieved through the following technical solution: A SiC@Ag heterojunction filler includes a SiC semiconductor core and an Ag metal shell covering the surface of the SiC semiconductor core; An Ag / SiC metal-semiconductor heterostructure is formed between the SiC semiconductor core and the Ag metal shell; The surface of the SiC semiconductor core has a nanoscale rough structure formed by etching with a composite roughening system of HF and NH4F.
[0007] Preferably, the average particle size of the SiC semiconductor core is 1–20 μm.
[0008] Based on the same inventive concept, this invention also provides a method for preparing SiC@Ag heterojunction fillers, comprising the following steps: SiC particles are added to an organic solvent for degreasing treatment; The degreasing SiC particles were roughened using a composite roughening system of HF and NH4F. The roughened SiC particles were sensitized using a sensitizing solution prepared with SnCl2 and hydrochloric acid. The sensitized SiC particles are added to a plating solution composed of a mixture of silver ammonia complex solution and composite reducing solution to perform a chemical silver plating reaction, thereby obtaining the SiC@Ag heterojunction filler as described in claim 1 or 2. The composite reducing solution contains glucose, tartaric acid, and anhydrous ethanol. Preferably, the organic solvent includes anhydrous ethanol.
[0009] Preferably, in the roughening treatment, the amount of 40% HF solution used is 60-150g per 100g of SiC, and the amount of NH4F added is 20-80g.
[0010] Preferably, the roughening process takes 20 to 90 minutes.
[0011] Preferably, in the sensitization treatment, the amount of SnCl2·2H2O used is 5-25g per 500mL of sensitizing solution, and the pH of the sensitizing solution is 1-2.
[0012] Preferably, the sensitization treatment time is 2 to 15 minutes.
[0013] Preferably, in the plating solution, the final concentration of AgNO3 is 1-6 g / L, the final concentration of glucose is 4-16 g / L, and the final concentration of tartaric acid is 4-16 g / L.
[0014] Preferably, the volume fraction of anhydrous ethanol in the plating solution is 5% to 20%.
[0015] Preferably, the volume ratio of the silver ammonia complex solution to the composite reducing solution is 0.8:1 to 1.2:1.
[0016] Preferably, the pH of the chemical silver plating reaction system is 9.0–11.0, the silver plating temperature is 20–35°C, and the silver plating time is 10–60 min.
[0017] Preferably, in the chemical silver plating reaction, the loading amount of sensitized SiC particles in the plating solution is 10–60 g / L.
[0018] Based on the same inventive concept, the present invention also provides a nonlinear conductive composite insulating coating, comprising an organosilicon resin matrix and the SiC@Ag heterojunction filler dispersed in the organosilicon resin matrix.
[0019] Preferably, the silicone resin matrix comprises 100 parts by weight, and the SiC@Ag heterojunction filler comprises 20 to 40 parts by weight.
[0020] Based on the same inventive concept, the present invention also provides a method for preparing a nonlinear conductive composite insulating coating, the method comprising the following steps: mixing organosilicon resin, the SiC@Ag heterojunction filler, coupling agent and curing agent, and sequentially performing dispersion, degassing, coating and curing steps to obtain the nonlinear conductive composite insulating coating.
[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention achieves uniform, dense, and highly adhesive silver deposition on SiC particle surfaces through synergistic control of pretreatment processes and plating solution systems, and imparts a significant nonlinear conductivity effect to the composite coating. Firstly, addressing the issues of chemical inertness and the natural oxide layer hindering metal deposition on the SiC surface, this invention employs a composite roughening system of HF and NH4F for pretreatment. The principle is that HF effectively dissolves the SiO2 oxide layer on the SiC surface, while the addition of NH4F not only provides a fluoride ion buffer to maintain etching stability but also etches nanoscale rough structures and micro-pits on the particle surface. This micro-roughness significantly increases the contact area for silver deposition and forms a strong mechanical interlock between the silver layer and the SiC substrate, effectively solving the technical problems of weak adhesion between the silver layer and the substrate, and easy detachment or local peeling in existing technologies. Based on this, this invention uses a SnCl2 / HCl sensitization system, utilizing Sn... 2+ The uniform adsorption characteristics under acidic conditions enable the in-situ construction of high-density catalytic active sites on the roughened surface. The principle is to provide the necessary nucleation centers for subsequent electroless silver plating, overcoming the problems of insufficient nucleation and localized missed plating caused by the lack of catalytic activity on the SiC surface, and ensuring full coverage and uniform nucleation of the silver layer.
[0022] Secondly, addressing the problem of uncontrollable deposition rates leading to rough coatings in traditional silver plating systems, this invention designs a plating solution combining a silver ammonia complex system and a glucose-tartaric acid composite reduction system, and introduces an ethanol component. The silver ammonia complex system precisely controls the concentration of free Ag+ ions in the plating solution through strong complexation, preventing the spontaneous and rapid precipitation of silver ions in the solution. The composite reduction system composed of glucose and tartaric acid provides a gentle and continuous reduction driving force through synergistic reduction, suppressing localized explosive deposition. Simultaneously, the addition of ethanol improves the wettability of the particle surface, reduces interfacial tension, and ensures good dispersion of SiC in the plating solution. This plating solution system controls the silver deposition rate and nucleation growth process from both thermodynamic and kinetic dimensions, ultimately achieving uniform and dense silver deposition on the particle surface, completely solving the technical defects of uneven coating thickness, silver agglomeration, and discrete conductivity behavior.
[0023] Finally, the SiC@Ag heterojunction filler obtained from the high-quality deposition was introduced into the silicone resin matrix. The principle lies in the construction of numerous Ag / SiC metal-semiconductor heterojunction interfaces between the SiC semiconductor core and the Ag metal shell. These interfaces exhibit significant field-response barrier characteristics under an electric field. Under low applied electric fields, the interface barrier is high, strongly blocking carrier transport and maintaining high insulation of the composite coating. When the applied electric field increases to a certain threshold, the interface barrier height decreases, allowing carriers to easily cross the interface, promoting rapid interconnection of local conductive networks between the fillers and a sharp increase in conductivity. This microscopic mechanism based on heterojunction barrier regulation endows the composite coating with a macroscopic nonlinear conductivity effect of "low-field insulation and high-field conduction," solving the application problems of traditional coatings where conductivity improvement is not significant under high fields and where electric field homogenization and stress relief cannot be achieved. Attached Figure Description
[0024] Figure 1 The conductivity curves are for embodiments 1-6 of the present invention. Detailed Implementation
[0025] The technical solution will be further described below with reference to the accompanying drawings and specific embodiments to help understand the content of the present invention.
[0026] The purpose of this invention is to provide a method for preparing SiC@Ag heterojunction filler to solve the problems of poor coating uniformity, weak adhesion between silver layer and substrate, poor pretreatment compatibility and insufficient controllability of plating solution in the prior art of chemical silver plating of SiC particles, so as to achieve uniform, dense and highly adhesive silver layer deposition on SiC surface.
[0027] Another objective of this invention is to provide a nonlinear conductive composite insulating coating containing the aforementioned SiC@Ag heterojunction filler. This coating uses silicone resin as a matrix and utilizes the Ag / SiC metal-semiconductor heterojunction interface in the SiC@Ag filler to maintain high insulation under low-field conditions and rapidly construct conductive pathways and improve conductivity under high-field conditions. This results in a significant nonlinear conductive effect in the composite coating, which can be used in fields such as electric field modulation, voltage equalization and slow release, and high-voltage insulation protection.
[0028] Example 1 (Parameter Minimum Dominant Type) A SiC@Ag heterojunction filler includes a SiC semiconductor core and an Ag metal shell covering the surface of the SiC semiconductor core; an Ag / SiC metal-semiconductor heterojunction interface is formed between the SiC semiconductor core and the Ag metal shell; the surface of the SiC semiconductor core has a nanoscale rough structure formed by etching with a composite roughening system of HF and NH4F.
[0029] Preferably, the average particle size of the SiC semiconductor core is 1–20 μm.
[0030] The specific implementation steps are as follows: 1) Degreasing treatment: Take 100 g of SiC particles with an average particle size of 1 μm, add them to 300 mL of anhydrous ethanol, stir at 500 r / min for 15 min, then sonicate for 10 min, wash twice with deionized water, and dry at 40℃ for 1 h.
[0031] 2) Roughening treatment: For 100 g SiC, add 60 g 40% HF solution and 20 g NH4F, add deionized water to 500 mL, roughen at 20℃ for 20 min at 500 r / min, wash 3 times, and dry at 40℃ for 1 h.
[0032] 3) Sensitization treatment: Dissolve 5 g of SnCl2·2H2O in 500 mL of deionized water and adjust the pH to 2 with concentrated hydrochloric acid. Add 5 g of roughened SiC and sensitize at 500 r / min for 2 min.
[0033] 4) Electroless silver plating: A mixed plating solution was prepared with the following concentrations: AgNO3 final concentration 1 g / L, glucose final concentration 4 g / L, tartaric acid final concentration 4 g / L, ethanol volume fraction 5%, A solution to B volume ratio 0.8:1, and pH 9.0. Sensitized SiC was added at a loading of 10 g / L, and the reaction was carried out at 20℃ and 500 r / min for 10 min. After washing three times, the mixture was dried at 30℃ to obtain SiC@Ag heterojunction filler.
[0034] 5) Coating preparation: Take 100 g of silicone resin, add 30 g of the above filler, 2 g of KH-550 silane coupling agent and 5 g of curing agent, mechanically disperse for 20 min, sonicate for 10 min, vacuum degas for 15 min, the wet film thickness is 200 μm, pre-cur at 80℃ for 30 min, and then cure at 120℃ for 2 h to obtain composite insulating coating.
[0035] 6) Coating nonlinear conductivity performance test: see Figure 1 Compared with the composite coating prepared directly from unmodified SiC (Comparative Example 6), the SiC@Ag modified organosilicon composite coating exhibits a significant nonlinear conductivity effect.
[0036] Example 2 (low median parameter type) This invention provides a method for preparing SiC@Ag heterojunction filler, including degreasing, roughening, sensitization and chemical silver plating steps.
[0037] Step 1: Degreasing treatment SiC particles were added to anhydrous ethanol for stirring and cleaning, followed by ultrasonic dispersion. They were then washed with deionized water and dried to remove organic oil, adsorbed pollutants, and loose deposits from the particle surface, reduce particle agglomeration tendency, improve particle surface cleanliness, and provide conditions for subsequent roughening and sensitization treatments.
[0038] The main parameter ranges affecting the technical effect are as follows: The average particle size of SiC particles is 1–20 μm, preferably 3–10 μm. Based on 100 g SiC, the amount of anhydrous ethanol added is 300–800 mL, preferably 400–600 mL; Stirring speed: 500-1200 r / min, preferably 700-1000 r / min; Stirring time: 15–60 min, preferably 20–40 min; Ultrasound time: 10–60 min, preferably 20–40 min; Number of deionized water rinses: 2 to 5 times, preferably 3 times; Drying temperature: 40-80℃, preferably 50-70℃; Drying time: 1 to 6 hours, preferably 2 to 4 hours.
[0039] Step 2: Roughening treatment The degreased SiC particles were treated with a composite roughening system of HF and NH4F to remove the naturally formed SiO2 oxide layer on the particle surface and to construct a nanoscale rough structure and micro-pits on the particle surface, thereby increasing the contact area for subsequent silver deposition and enhancing the mechanical interlocking effect and interfacial bonding strength between the coating and the substrate.
[0040] The main parameter ranges affecting the technical effect are as follows: Based on 100 g of SiC, the amount of 40% HF solution used is 60–150 g, preferably 80–120 g; NH4F addition amount: 20-80 g, preferably 30-60 g; The total volume of the roughening solution after adding deionized water is 500–1500 mL, preferably 800–1200 mL. Stirring speed: 500-1200 r / min, preferably 700-1000 r / min; Roughening temperature: 20~35℃; Roughening time: 20–90 min, preferably 40–70 min; Number of deionized water rinsings after roughening: 3 to 6 times, preferably 3 times; Drying temperature: 40-80℃, preferably 50-70℃; Drying time: 1 to 6 hours, preferably 2 to 4 hours.
[0041] Step 3: Sensitization treatment SnCl₂·2H₂O was dissolved in deionized water, and the pH of the solution was adjusted to the acidic range using concentrated hydrochloric acid to prepare the sensitizing solution. The coarsened SiC particles were then added to the sensitizing solution to allow the Sn²⁺ particles to precipitate. + Uniform adsorption on the particle surface constructs the catalytic active sites required for subsequent silver deposition.
[0042] The main parameter ranges affecting the technical effect are as follows: Based on 500 mL of sensitizing solution, the amount of SnCl2·2H2O used is 5–25 g, preferably 10–18 g; Sensitization solution pH: 1-2; Based on 500 mL of sensitizing solution, the amount of roughened SiC particles added is 5–25 g. Stirring speed: 500-1200 r / min, preferably 700-1000 r / min; Sensitization time: 2–15 min, preferably 3–8 min; Sensitization temperature: 20–35℃; Cleaning frequency: 1-2 times; Post-sensitization treatment: Do not dry or dry at low temperature for a short time and then immediately proceed to the silver plating step.
[0043] Step 4: Chemical silver plating treatment The chemical silver plating process includes two steps: plating solution preparation and silver plating reaction.
[0044] Solution A is a silver-ammonia complex solution, prepared by mixing AgNO3, ammonia, and NaOH; Solution B is a composite reducing solution, prepared by mixing glucose, tartaric acid, anhydrous ethanol, and deionized water. After mixing Solutions A and B, the pH of the system is adjusted, and sensitized SiC particles are added to initiate the reaction, allowing the silver layer to be uniformly deposited on the particle surface, ultimately yielding the SiC@Ag heterojunction filler.
[0045] The main parameter ranges affecting the technical effect are as follows: Final concentration of AgNO3 in solution A (based on mixed plating solution): 1–6 g / L, preferably 1.5–3.5 g / L; Final glucose concentration in solution B (based on mixed plating solution): 4–16 g / L, preferably 6–12 g / L; The final concentration of tartaric acid in solution B (based on the mixed plating solution): 4–16 g / L, preferably 6–12 g / L; The volume fraction of ethanol in the mixed plating solution is 5%–20%, preferably 8%–15%. The volume ratio of liquid A to liquid B is 0.8:1 to 1.2:1, preferably 1:1; The pH of the silver plating system is 9.0–11.0, preferably 9.5–10.5; Silver plating temperature: 20~35℃, preferably 20~30℃; Stirring speed: 500-1200 r / min, preferably 700-1000 r / min; Silver plating time: 10–60 min, preferably 20–40 min; The loading of sensitized SiC particles in the plating solution is 10–60 g / L, preferably 20–40 g / L. Number of times to wash with deionized water after reaction: 3 to 5 times; Drying temperature: 30-60℃, preferably 35-45℃; Drying time: 1 to 6 hours.
[0046] In this step, the silver ammonia complex system can regulate free Ag. + Concentration is used to prevent rapid precipitation of silver ions; the glucose-tartaric acid composite reduction system can achieve a smoother and more uniform silver deposition; ethanol helps to improve the wettability and dispersion of the particle surface, thereby improving the uniformity of the coating and inhibiting agglomeration.
[0047] A typical implementation process is as follows: 1) Degreasing treatment: Take 100 g of SiC particles with an average particle size of 3 μm, add 400 mL of anhydrous ethanol, stir at 700 r / min for 20 min, sonicate for 20 min, wash 3 times, and dry at 50℃ for 2 h.
[0048] 2) Roughening treatment: Add 80 g of 40% HF solution and 30 g of NH4F, add deionized water to 800 mL, and roughen at 25℃ for 40 min at 700 r / min.
[0049] 3) Sensitization treatment: Take 10 g SnCl2·2H2O to prepare 500 mL of sensitization solution and adjust the pH to 1.8; add 10 g of roughened SiC and sensitize at 700 r / min for 3 min.
[0050] 4) Chemical silver plating: The final concentration of AgNO3 is 1.5 g / L, the final concentration of glucose is 6 g / L, the final concentration of tartaric acid is 6 g / L, the volume fraction of ethanol is 8%, the volume ratio of solution A to solution B is 1:1, the pH of the system is 9.5, the reaction is carried out at 25℃ and 700 r / min for 20 min, and the loading amount is 20 g / L.
[0051] 5) Coating preparation: Take 100 g of silicone resin, add 30 g of the above filler, 2 g of KH-550 silane coupling agent and 5 g of curing agent, mechanically disperse for 20 min, sonicate for 10 min, vacuum degas for 15 min, the wet film thickness is 200 μm, pre-cur at 80℃ for 30 min, and then cure at 120℃ for 2 h to obtain composite insulating coating.
[0052] 6) Coating nonlinear conductivity performance test: see Figure 1 Compared with the composite coating prepared directly from unmodified SiC (Comparative Example 6), the SiC@Ag modified organosilicon composite coating exhibits a significant nonlinear conductivity effect.
[0053] To address the chemical inertness and tendency to agglomerate of SiC surfaces, this invention establishes a highly adaptable pretreatment process. Through the synergistic effects of degreasing, roughening, and sensitization, organic contaminants and oxide layers on the SiC surface are effectively removed, and uniform catalytic active sites are constructed on the particle surface, thus providing a good foundation for the subsequent uniform deposition of silver layers. Based on this, this invention employs a plating bath design combining a silver-ammonia complex system and a glucose-tartaric acid composite reduction system. This effectively controls the concentration of free silver ions and the deposition rate, reducing the problems of coarse silver layer agglomeration and localized incomplete plating, achieving uniform, dense, and highly adhesive silver layer deposition on the SiC surface. This deposition method facilitates the construction of numerous Ag / SiC metal-semiconductor heterojunctions between SiC semiconductor particles and highly conductive Ag metal. These heterojunctions not only improve the conductive shell structure of the filler but also provide an important foundation for the subsequent construction of a nonlinear conductive mechanism in the composite system. Finally, after the prepared SiC@Ag heterojunction filler is introduced into the organosilicon resin matrix, the composite system can maintain insulation properties under low electric field, while gradually establishing a conductive path and rapidly increasing conductivity under high electric field. It exhibits a significant nonlinear conductivity effect of "insulation under low field and conduction under high field", and can be widely used in electric field homogenization, stress relief and high voltage insulation protection.
[0054] The main reaction process of this invention can be completed under normal pressure, low temperature or room temperature conditions, with low equipment requirements and good process repeatability, making it suitable for the large-scale preparation of SiC@Ag heterojunction fillers and their composite insulating coatings.
[0055] Example 3 (Intermediate Parameter Type) The present invention also provides a nonlinear conductive composite insulating coating, comprising an organosilicon resin matrix and the aforementioned SiC@Ag heterojunction filler dispersed therein. The SiC@Ag heterojunction filler consists of a SiC semiconductor particle core and a surface Ag metal shell, forming a large number of Ag / SiC metal-semiconductor heterojunction interfaces between them.
[0056] When this filler is introduced into the silicone resin matrix, the Ag shell can improve the contact probability between fillers and the ability to build conductive pathways, while the Ag / SiC interface can form a field-response barrier structure. Under a low applied electric field, the interface barrier inhibits carrier transport, and the composite coating maintains high overall volume resistivity and insulation performance. When the applied electric field increases to a certain level, the interface barrier height decreases, and carriers can more easily cross the interface. The local conductive network in the composite system is rapidly connected, and the conductivity is significantly improved, thus exhibiting a significant nonlinear conductivity effect.
[0057] In this invention, the composite insulating coating is prepared using the following specific process: Take 100 g of silicone resin, add 30 g of SiC@Ag heterojunction filler, 2 g of KH-550 silane coupling agent and 5 g of curing agent, stir mechanically for 20 min, then ultrasonically disperse for 10 min, vacuum degas for 15 min and then uniformly coat it on the substrate surface, control the wet film thickness to 200 μm, pre-cur at 80℃ for 30 min, and then cure at 120℃ for 2 h to obtain a nonlinear conductive composite insulating coating.
[0058] The specific implementation process is as follows: 1) Degreasing treatment: Take 100 g of SiC particles with an average particle size of 6.5 μm, add them to 500 mL of anhydrous ethanol, stir at 900 r / min for 30 min, then ultrasonically disperse for 30 min, wash with deionized water 3 times, and dry at 60℃ for 2 h.
[0059] 2) Roughening treatment: Add 100 g of 40% HF solution and 40 g of NH4F, add deionized water to 1000 mL, roughen at 25℃ for 60 min at 900 r / min, wash 3 times, and dry at 60℃ for 2 h.
[0060] 3) Sensitization treatment: Dissolve 15 g SnCl2·2H2O in 500 mL of deionized water and adjust the pH to 1-2 with concentrated hydrochloric acid; add 25 g of roughened SiC and sensitize at 900 r / min for 5 min.
[0061] 4) Chemical silver plating: Solution A: Prepare AgNO3 solution, adjust the volume with ammonia and NaOH, and then make up to a final volume; Solution B: Take 4 g of glucose and 4 g of tartaric acid, and add distilled water and anhydrous ethanol according to the process requirements to prepare the solution; Solution A and solution B were mixed at a 1:1 volume ratio, and the pH was adjusted to 10 to achieve a final AgNO3 concentration of 2 g / L, a final glucose and tartaric acid concentration of 8 g / L, and an ethanol volume fraction of 12.5%. Sensitized SiC was added at a loading of 25 g / L, and the reaction was carried out at room temperature and 900 r / min for 30 min. After the reaction, the mixture was filtered, washed three times, and dried at 40℃ to obtain the SiC@Ag heterojunction filler.
[0062] 5) Coating preparation: Take 100 g of silicone resin, add 30 g of the above filler, 2 g of KH-550 silane coupling agent and 5 g of curing agent, mechanically disperse for 20 min, sonicate for 10 min, vacuum degas for 15 min, the wet film thickness is 200 μm, pre-cur at 80℃ for 30 min, and then cure at 120℃ for 2 h to obtain composite insulating coating.
[0063] 6) Coating nonlinear conductivity performance test: see Figure 1 Compared with the composite coating prepared directly from unmodified SiC (Comparative Example 6), the SiC@Ag modified organosilicon composite coating exhibits a significant nonlinear conductivity effect.
[0064] Example 4 (High-Temperature Parameter Type) 1) Degreasing treatment: Take 100 g of SiC particles with an average particle size of 10 μm, add 600 mL of anhydrous ethanol, stir at 1000 r / min for 40 min, sonicate for 40 min, wash 3 times, and dry at 70℃ for 3 h.
[0065] 2) Roughening treatment: Add 120 g of 40% HF solution and 60 g of NH4F, add deionized water to 1200 mL, and roughen at 30℃ for 70 min at 1000 r / min.
[0066] 3) Sensitization treatment: Take 18 g SnCl2·2H2O to prepare 500 mL sensitization solution with pH 1.2, add 20 g of roughened SiC, and sensitize for 6 min at 1000 r / min.
[0067] 4) Chemical silver plating: The final concentration of AgNO3 is 3.5 g / L, the final concentrations of glucose and tartaric acid are both 10 g / L, the volume fraction of ethanol is 15%, the volume ratio of solution A to solution B is 1:1, the pH of the system is 10.5, the reaction is carried out at 30℃ and 950 r / min for 40 min, and the loading amount is 35 g / L.
[0068] 5) Coating preparation: Take 100 g of silicone resin, add 30 g of the above filler, 2 g of KH-550 and 5 g of curing agent, mechanically disperse for 20 min, sonicate for 10 min, vacuum degas for 15 min, the wet film thickness is 200 μm, pre-cur at 80℃ for 30 min, and then cure at 120℃ for 2 h to obtain composite insulating coating.
[0069] 6) Coating nonlinear conductivity performance test: see Figure 1 Compared with the composite coating prepared directly from unmodified SiC (Comparative Example 6), the SiC@Ag modified organosilicon composite coating exhibits a significant nonlinear conductivity effect.
[0070] Example 5 (Parameter Maximum Value Dominant Type) 1) Degreasing treatment: Take 100 g of SiC particles with an average particle size of 20 μm, add 800 mL of anhydrous ethanol, stir at 1200 r / min for 60 min, sonicate for 60 min, wash 5 times, and dry at 80℃ for 6 h.
[0071] 2) Roughening treatment: Add 150 g of 40% HF solution and 80 g of NH4F, add deionized water to 1500 mL, and roughen at 35 °C for 90 min at 1200 r / min.
[0072] 3) Sensitization treatment: Take 25 g SnCl2·2H2O to prepare 500 mL of sensitization solution with pH 1.0, add 25 g of roughened SiC, and sensitize for 15 min at 1200 r / min.
[0073] 4) Chemical silver plating: The final concentration of AgNO3 is 6 g / L, the final concentrations of glucose and tartaric acid are both 16 g / L, the volume fraction of ethanol is 20%, the volume ratio of solution A to solution B is 1.2:1, the pH of the system is 11.0, the reaction is carried out at 35℃ and 1200 r / min for 60 min, and the loading amount is 60 g / L.
[0074] 5) Coating preparation: Take 100 g of silicone resin, add 30 g of the above filler, 2 g of KH-550 and 5 g of curing agent, mechanically disperse for 20 min, sonicate for 10 min, vacuum degas for 15 min, the wet film thickness is 200 μm, pre-cur at 80℃ for 30 min, and then cure at 120℃ for 2 h to obtain composite insulating coating.
[0075] 6) Coating nonlinear conductivity performance test: see Figure 1Compared with the composite coating prepared directly from unmodified SiC (Comparative Example 6), the SiC@Ag modified organosilicon composite coating exhibits a significant nonlinear conductivity effect.
[0076] Example 6 (Preferred Implementation) 1) Degreasing treatment: Take 100 g of SiC particles with an average particle size of 5-8 μm, add them to 500 mL of anhydrous ethanol, stir at 800-1000 r / min for 25-35 min, sonicate for 20-30 min, wash 3 times, and dry at 55-65℃ for 2-3 h.
[0077] 2) Roughening treatment: Add 90-110 g of 40% HF solution and 35-50 g of NH4F, add deionized water to 900-1100 mL, and roughen at 20-30℃ for 50-70 min at 800-1000 r / min.
[0078] 3) Sensitization treatment: Take 12-18 g of SnCl2·2H2O to prepare 500 mL of sensitization solution with a pH of 1.2-1.8, add 15-25 g of roughened SiC, and sensitize at 800-1000 r / min for 4-6 min.
[0079] 4) Chemical silver plating: final concentration of AgNO3 1.5-3.0 g / L, final concentration of glucose and tartaric acid 6-10 g / L, ethanol volume fraction 10%-15%, volume ratio of solution A to solution B 1:1, system pH 9.8-10.3, loading amount 20-35 g / L, reaction at 20-30℃ for 20-35 min.
[0080] 5) Coating preparation: Take 100 g of silicone resin, add 30 g of the above filler, 2 g of KH-550 and 5 g of curing agent, mechanically disperse for 20 min, sonicate for 10 min, vacuum degas for 15 min, the wet film thickness is 200 μm, pre-cur at 80℃ for 30 min, and then cure at 120℃ for 2 h to obtain composite insulating coating.
[0081] 6) Coating nonlinear conductivity performance test: see Figure 1 Compared with the composite coating prepared directly from unmodified SiC (Comparative Example 6), the SiC@Ag modified organosilicon composite coating exhibits a significant nonlinear conductivity effect.
[0082] VI. Comparative Examples (to verify the beneficial effects of the invention). Comparative Example 1: Omitting the roughening step (a key inventive point in destroying the deoxide layer and constructing a rough interface) 1.1 Process Design After completing the degreasing treatment as in Example 3, without HF / NH4F roughening, the process proceeds directly to the sensitization and chemical silver plating steps, with the remaining conditions being the same as in Example 3.
[0083] 1.2 Defect Manifestations Because the natural oxide layer on the SiC surface was not effectively removed, the particle surface lacked a rough interface and active sites suitable for silver deposition, resulting in sensitized Sn²⁺… + The adsorption capacity is low and unevenly distributed.
[0084] 1.3 Performance Defects Insufficient silver nucleation on the particle surface resulted in significant localized plating defects and poor coating continuity. When used to prepare composite coatings, insufficient conductive pathways were constructed under high fields, leading to a weakened nonlinear conductivity response. This indicates that the roughening step plays a crucial role in improving the adhesion and coverage of the silver layer.
[0085] Comparative Example 2: The sensitization step was omitted (a key inventive point that disrupts the construction of catalytic active sites). 2.1 Process Design After completing the degreasing and roughening treatment according to Example 3, without sensitization, the sample was directly added to the chemical silver plating solution for reaction, with all other conditions remaining the same.
[0086] 2.2 Defect Manifestations Because the SiC surface lacks sufficient catalytic active sites, the silver layer can only be preferentially deposited in a few local areas, making it difficult to achieve full and uniform coating.
[0087] 2.3 Performance Defects The silver layer on the particle surface is distributed in a discrete island pattern, with obvious surface agglomeration. After being used to prepare a composite coating, the continuity of the electrical conductivity network is insufficient, and the slope of the nonlinear conductivity curve is small. This indicates that the sensitization step is a necessary condition for obtaining a uniform silver layer.
[0088] Comparative Example 3: The pH of the silver plating system is below the lower limit (a key invention that disrupts the balance between silver deposition rate and complexation). 3.1 Process Design Pretreatment was performed according to Example 3. During the silver plating reaction, the pH of the mixed plating solution was adjusted to 8.5, which is lower than the range of 9.0 to 11.0 defined in this invention, while the other conditions remained unchanged.
[0089] 3.2 Defect Manifestations At lower pH conditions, the stability of the silver ammonia complex system and the reduction reaction rate are mismatched, and free Ag... + Insufficient release and reduction deposition rates make it difficult for the silver layer to form a continuous coating within the specified time.
[0090] 3.3 Performance Defects The silver content on the particle surface is low, resulting in significant local exposure of the SiC substrate. Conductive pathways in the composite coating are difficult to establish fully, leading to limited conductivity improvement under high fields. This indicates that controlling the pH of the silver plating system within the range specified in this invention is crucial for uniform silver deposition.
[0091] Comparative Example 4: The pH and AgNO3 concentration of the silver plating system were higher than the upper limit (a key invention point that disrupts the uniformity of deposition). 4.1 Process Design Pretreatment was performed according to Example 3. During the silver plating reaction, the final concentration of AgNO3 was increased to 7 g / L, and the pH of the system was increased to 11.5, both of which exceeded the limits of this invention. All other conditions were the same.
[0092] 4.2 Defect Manifestations Excessive concentration of free silver ions and strong alkalinity lead to rapid precipitation of silver in the solution and on the surface of particles, resulting in uncontrolled deposition rate and the formation of coarse silver particles and local agglomeration.
[0093] 4.3 Performance Defects The silver layer on the particle surface is rough and uneven in thickness, with silver agglomeration in some areas; the low-field resistivity of the composite coating decreases too rapidly, the high-field conductivity exhibits increased dispersion, and the nonlinear conductivity stability deteriorates. This indicates that the AgNO3 concentration and pH range specified in this invention are beneficial for obtaining a uniform silver layer.
[0094] Comparative Example 5: Ethanol component omitted (a key invention that disrupts particle wetting and dispersion control) 5.1 Process Design Pretreatment was performed according to Example 3. When preparing solution B, anhydrous ethanol was not added, and only deionized water was used. All other conditions were the same.
[0095] 5.2 Defect Manifestations Due to the decreased wettability and dispersibility of the particle surface, SiC is more prone to agglomeration in the plating solution, resulting in uneven mass transfer in certain areas and affecting the uniform deposition of the silver layer.
[0096] 5.3 Performance Defects The uniformity of the silver layer coverage on the particle surface decreased, with thicker coatings in agglomerated areas and thinner coatings in dispersed areas; the filler dispersion in the composite coating deteriorated, and the nonlinear conductive pathways were unevenly constructed. This indicates that the ethanol component plays an important role in improving the wetting of the plating solution and particle dispersion.
[0097] Comparative Example 6: Composite insulating coatings were prepared directly using unmodified SiC (to verify the necessity of surface metallization modification). 6.1 Process Design Raw SiC particles that have not undergone degreasing, roughening, sensitization, and chemical silver plating were directly added to organosilicon resin to prepare a composite insulating coating, following the coating preparation method in Example 3.
[0098] 6.2 Defect Manifestations The original SiC particles have no Ag shell on their surface and do not have an Ag / SiC heterostructure. In polymer systems, they only behave as ordinary semiconductor inorganic fillers.
[0099] 6.3 Performance Defects The resulting coating exhibits minimal conductivity variation across the entire test electric field range, with only minor conductivity enhancement at high fields, making it difficult to demonstrate a prominent nonlinear conductivity effect. This indicates that surface silver plating modification of SiC and the construction of an Ag / SiC heterostructure are crucial prerequisites for obtaining a nonlinear conductive composite insulating coating.
[0100] In summary, compared with Examples 1-6, Comparative Examples 1-6 compromised the key technical features of the present invention in several ways, including omitting roughening, lacking sensitization, having a low silver plating pH, high AgNO3 concentration and pH, lacking ethanol components, and directly applying unmodified SiC. These compromises resulted in varying degrees of problems such as discontinuous silver deposition, uneven coverage, significant agglomeration, or weakened nonlinear conductivity of the composite coating. The above results demonstrate that the pretreatment and electroless silver plating parameter ranges defined in this invention, and the resulting SiC@Ag heterostructure, are necessary conditions for achieving uniform and dense silver deposition and a significantly nonlinear conductive composite insulating coating.
[0101] This invention provides a dedicated "degreasing-roughening-sensitization-chemical silver plating" process route for SiC particles. In this route, an HF / NH4F composite roughening system is used to effectively remove the oxide layer on the SiC surface and construct a nanoscale roughened interface. Subsequently, a SnCl2 / HCl sensitization system is used to uniformly introduce catalytically active sites required for subsequent silver deposition onto the SiC surface. In the chemical silver plating stage, a plating solution design combining a silver-ammonia complex system and a glucose-tartaric acid composite reduction system is employed to achieve a relatively smooth and uniform silver layer deposition. Through the above process, a SiC@Ag heterojunction filler with an Ag shell and a SiC semiconductor core is finally obtained, which can construct a field-responsive conductive network within the polymer. Based on this, this invention also provides a nonlinear conductive composite insulating coating containing the above heterojunction filler, enabling the material to simultaneously possess insulation and high field conductivity responsiveness.
[0102] The above are merely embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention are included within the scope of the claims of the present invention.
Claims
1. A SiC@Ag heterojunction filler, characterized in that, It includes a SiC semiconductor core and an Ag metal shell covering the surface of the SiC semiconductor core; An Ag / SiC metal-semiconductor heterostructure is formed between the SiC semiconductor core and the Ag metal shell; The surface of the SiC semiconductor core has a nanoscale rough structure formed by etching with a composite roughening system of HF and NH4F.
2. The SiC@Ag heterojunction filler according to claim 1, characterized in that, The average particle size of the SiC semiconductor core is 1–20 μm.
3. A method for preparing SiC@Ag heterojunction filler, characterized in that, Includes the following steps: SiC particles are added to an organic solvent for degreasing treatment; The degreasing SiC particles were roughened using a composite roughening system of HF and NH4F. The roughened SiC particles were sensitized using a sensitizing solution prepared with SnCl2 and hydrochloric acid. The sensitized SiC particles are added to a plating solution composed of a mixture of silver ammonia complex solution and composite reducing solution to perform a chemical silver plating reaction, thereby obtaining the SiC@Ag heterojunction filler as described in claim 1 or 2. The composite reducing solution contains glucose, tartaric acid, and anhydrous ethanol.
4. The preparation method according to claim 3, characterized in that, The organic solvent includes anhydrous ethanol.
5. The preparation method according to claim 3, characterized in that, In the roughening treatment, based on 100g of SiC, the amount of 40% HF solution used is 60-150g, and the amount of NH4F added is 20-80g.
6. The preparation method according to claim 5, characterized in that, The roughening process takes 20 to 90 minutes.
7. The preparation method according to claim 3, characterized in that, In the sensitization treatment, based on 500 mL of sensitizing solution, the amount of SnCl2·2H2O used is 5–25 g, and the pH of the sensitizing solution is 1–2.
8. The preparation method according to claim 7, characterized in that, The sensitization treatment time is 2 to 15 minutes.
9. The preparation method according to claim 3, characterized in that, In the plating solution, the final concentration of AgNO3 is 1–6 g / L, the final concentration of glucose is 4–16 g / L, and the final concentration of tartaric acid is 4–16 g / L.
10. The preparation method according to claim 9, characterized in that, The volume fraction of anhydrous ethanol in the plating solution is 5% to 20%.
11. The preparation method according to claim 9, characterized in that, The volume ratio of the silver ammonia complex solution to the composite reducing solution is 0.8:1 to 1.2:
1.
12. The preparation method according to claim 3, characterized in that, The chemical silver plating reaction system has a pH of 9.0–11.0, a plating temperature of 20–35°C, and a plating time of 10–60 min.
13. The preparation method according to claim 3, characterized in that, In the chemical silver plating reaction, the loading of sensitized SiC particles in the plating solution is 10–60 g / L.
14. A nonlinear conductive composite insulating coating, characterized in that, It includes an organosilicon resin matrix and the SiC@Ag heterojunction filler as described in claim 1 or 2 dispersed in the organosilicon resin matrix.
15. The nonlinear conductive composite insulating coating according to claim 14, characterized in that, The silicone resin matrix comprises 100 parts by weight, and the SiC@Ag heterojunction filler comprises 20 to 40 parts by weight.
16. A method for preparing a nonlinear conductive composite insulating coating, characterized in that, The silicone resin, the SiC@Ag heterojunction filler as described in claim 1 or 2, the coupling agent and the curing agent are mixed and then subjected to dispersion, degassing, coating and curing steps in sequence to obtain the nonlinear conductive composite insulating coating as described in claim 14 or 15.